Untangling Leader-Member Exchange and Employee Envy: An Empirical Investigation Within the Indian IT Sector - Sunali Bindra; Bhumika Achhnani; Chitra Sharma; Bindiya Gupta; Sonali Bhattacharya (Australasian Accounting, Business and Finance Journal, 2025)
Within the framework of envy and its related consequences, this paper inspects the dynamics of superior-subordinate relationships, also known as Leader-member exchange, in the management literature. Based on the Leader-Member Exchange theory, we propose that employees lacking a strong camaraderie with their supervisors (low-quality LMX) will experience envy towards peers who enjoy a high-quality LMX with their supervisors. Subsequently, they will engage in uncivil behaviours and exhibit an "intention to quit." Hypotheses were tested using hierarchical regression on data obtained from two hundred and four software engineers in different Indian information technology (IT) companies. This study provides evidence in favour of all the suggested hypotheses and expands upon existing research on the subject by illustrating the adverse effects of envy in the workplace.
Keywords: Leader-Member Exchange; Employee Envy; Intention to Quit